GOVERNMENT HEALTH EXPENDITURE AND EDUCATIONAL OUTCOME IN NIGERIA: INTERROGATING THE NEXUS - Aishat Princess Umar; Mathew Rotimi Ekundayo; Naphtali W. John (International Studies Journal)
The study examined the nexus between government health expenditure and educational outcome in Nigeria from 1981 to 2021. To achieve this objective the study collected time series data on the relevant variables namely: government health expenditure, school enrolment ratio which was used as the proxy for educational outcome, infant mortality which chosen because it received the direct effect of a change in government health expenditure and the Gross Domestic Product of Nigeria. The study conducted a stationarity test using the Augmented Dickey Fuller Unit Root test and a long run relationship was tested with the aid of the Johansen test for integration. The study found all the variables to be stationary at first difference while thevariables were conitegrated at 5% level of significance. The Vector Autoregressive Model (VAR) was used to examine the interconnectedness of the variables and their relationships.It was however discovered that health expenditure in Nigeria had a positiveimpact on educational outcome.The findings of the paper revealed that government health expenditure can have positive impacts on school enrolment ratioin Nigeria depending on how significant the amount spent on the health sector is. This implies that as health expenditure rises, school enrolment ratio rises. The study recommended among other things that a significant portion of the Nigeria’s budget should be allocated to the health sector to generate a positive change in the educational sector.